(untitled) (LACCEI, 2024)
In Peru there are many roads where accidents occur due to their inadequate geometric design. The most incident traffic accidents are side crash or collision with a percentage of 42.73%, and confusion with 20.19% [1]. This shows that it is necessary to carry out a redesign in this road that seeks to reduce the percentage of accidents in the area. For the case study, a section of a 3km highway located in Santiago de Chuco north of the city of Lima was used. Thanks to the photogrammetric record made of the current state of the road, sectors with geometric deficiencies were identified, such as visibility distance and safety in terms of precariousness in the use of signage. Likewise, the evaluation carried out in the stopping and overtaking visibility distance concludes that with a constant speed of 30 km/h there are sections or sections that do not meet the necessary distance for its route